The Role of Chemotherapy and Radiotherapy in the Surgical Management of Muscle Invasive Bladder Cancer - Joshua Luck (University Library System, University of Pittsburgh, 2014)
The management of muscle invasive bladder cancer represents an unresolved clinical challenge. Invasive urothelial carcinomas are associated with high mortality rates and early metastatic disease. Radical cystectomy is a recognized standard of care, although disease-free survival outcomes remain suboptimal. The limitations of pre-operative clinical staging, as well as the complex natural history of the disease, precludes the introduction of simple management protocols. To what degree chemotherapy and radiotherapy may be useful in the surgical management of invasive bladder cancer remains contentious. This literature review critically examines the benefits, risks and difficulties of each approach, with an emphasis on individually tailored therapy.